(untitled) (International Journal of Nursing Education, 2020)
A study was done to determine the effectiveness of family intervention on relapse rate of persons with alcohol dependence syndrome, in selected De-addiction centre. Objectives were (1) Determine the effectiveness of family intervention on relapse rate of persons with alcohol dependence syndrome. (2) Identify the effectiveness of family intervention on Gamma Glutamyl Transferase (GGT) levels of persons with alcohol dependence syndrome. True experimental approach with pre test, post test control group design was used for 100 samples, 50 each of control and experimental groups by simple random sample. Research tools were structured questionnaire for personal data and AWARE (Advance Warning Signs of Relapse) scale. Friedman’s RM ANOVA on ranks by Dunn’s method and Mann Whitney rank sum test were used to evaluate the relapse rate of control and experimental groups. The pre test and post test GGT values of control and experimental groups were evaluated by unpaired ‘t’ test. The study concluded that family interventions was effective for reducing relapse rate, GGT level showed a significant decrease in the experimental group compared to control group.